Removal of Basic and Reactive Dyes by Sorption Using Ethylenediamine-Modified Rice Hull - Ong, Siew Teng (2006)
The effectiveness of using ethylenendiamine modified rice hull (MRH) to remove Basic Blue 3 (BB3) and Reactive Orange (RO16) from single and binary dye solutions was investigated. The optimised modification process was treating 1.00 g of rice hull with 0.02 mol of ethylendiamine (EDA) in a “well stirred” water bath at 80oC for 2 hours. Surface morphology analysis was carried out using scanning electron microscopy (SEM) and atomic force microscopy (AFM). Batch and column studies were performed under various experimental conditions and the parameters studied included pH, contact time, initial concentration, temperature, agitation rate, particle size, sorbent dosage, bed depth, flow-rate and sorption –desorption process. Batch studies reveal that sorption was pH and concentration dependent. The sorption of BB3 and RO16 from single and binary dye solution was found to be endothermic and exothermic, respectively. The kinetics of dye sorption fitted a pseudo-second order rate expression. Maximum sorption capacities calculated from the Langmuir model are 14.68 and 60.24 mg/g for BB3 and RO16, respectively in binary dye solutions. This corresponds to an enhancement of 4.5 and 2.4 folds, respectively, compared to single dye solutions. The dye uptake increased with increasing sorbent dosage. Column studies indicate that breakthrough was bed depth, flow rate and influent concentration dependent. Unusual breakthrough curves were obtained for RO16, with very rapid initial breakthrough followed by complete retention at low flow rate, influent concentration and high bed depth. The breakthrough curves of BB3 followed the typical S shape of packed- bed systems. Theoretical breakthrough curves at different bed depths and flow rates generated by the two parameter mathematical model agreed well with the experimental data of single dye solution of BB3. In sorption-desorption process, BB3 can be recovered completely by eluting the column with 0.5 M H2SO4 and HCl but the column cannot be reused. However the desorption of RO16 from MRH column was unsuccessful. The effect of initial concentrations as well as light source was investigated in the photodegradation of BB3 and RO16 using TiO2 catalyst. Both BB3 and RO16 can be degraded using suspended TiO2, with either UV or sunlight as the light source. In the removal of dyes using a combination of sorption and photodegradation, immobilized MRH and TiO2 were used. The percentage of dye removal increased with increasing irradiation time and the maximum number of dip coatings that can be applied was ten. MRH dip coated with TiO2 appeared to be less efficient to remove dyes compared to separate MRH and TiO2 plates. For all the dye solutions studied, the percentage of dye removal decreased with increasing number of usage of immobilized TiO2. Highest percentage of dyes removal was obtained when MRH/TiO2 glass plates were placed at a distance of 2.2 cm apart with air bubbling between them. In the study of treatment of wastewater from textile industry, optimum pH for the sorption of dyes using MRH was in the range of 2 to 5. Uptake of dye under both batch and continuous flow conditions shows similar behavior as in synthetic solutions. However, photodegradation of the dye from the wastewater was unsuccessful.